Pengaruh Perputaran Modal Kerja, Rasio Lancar, Dan Total Asset Turnover (TATO), Debt Rasio Terhadap Profitabilitas Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2019 - Theo Genki Matondang; Kerismawati Buulolo; Leni Priska Manurung; Friska Darnawaty Sitorus (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study uses a sample of 244 manufacturing companies by analyzing the performance of financial statements that have been audited by a public accountants for the period 2016 - 2019. This study uses secondary data namely the purposive sampling method with the R2 method. The results of this study identicate that working capital turnover, current ratio, total asset turn over ratio and debt ratio simultaneously have a significant effect on profitability. Partially, the debt ratio variable has no effect on profitability. While the variable Working capital turnover has a negative and significant effect on profitability. Current ratio has a positive and significant effect on profitability. TATO positive and significant effect on profitability The results of the coefficient of determination test obtained an adjusted R Square value of 0.150 or 15.0%, which means the dependent variable, namely profitability, can be explained by the third variation. The independent variables are cash turnover, working capital turnover and current ratio of 15.0%, while the remaining 75.0% is explained by other factors not examined in this research. Keywords: Working Capital Turnover, Current Ratio, TATO, Debt Ratio and Profitability.